Consumer Financial Exploitation of the Elderly in Arizona and Florida, 2010-2011 - Holtfreter, Kristy ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed.The objectives of the study were: (1) To determine the nature, incidence, and prevalence of fraud victimization among elderly consumers in Arizona and Florida; (2) To identify risk and protective factors associated with fraud victimization in this population; and (3) To evaluate the elderly population's awareness and use of state-based programs, including reporting behavior to law enforcement.The study is comprised of data from telephone surveys of 2,000 aged 60 years and older Arizona (n = 1,000) and Florida (n = 1,000). The survey was obtained via computer assisted telephone interviewing (CATI) administered by Precision Research in June and July of 2011. Data were collected seven days a week during specific times of the day that had the greatest probability of contacting a respondent. The interviews were primarily conducted in English but a Spanish survey instrument was constructed and used when necessary.